Book of the Just : book three of the Bohemian trilogy - Carpenter, Dana Chamblee (Carpenter, Dana Chamblee. Bohemian trilogy, 2018)
"After centuries of searching, Mouse now has everything shes ever wanted within her reacha normal life, a lover, a brother. What will she risk to keep them? Cherished by a Father, coveted by a king, loved by an almost-priest; tormented by demons, tortured by a madman, hunted by a cult, hounded by her father. Mouse has survived it all. But then, she was never just a girl. Despite Mouses power, her father always wanted a sonand now, at long last, he has him. And Mouse has a brother, someone else in the world just like her. Though shes never met him, the hope of what they might mean for each other tugs at her soul, even as it terrifies her lover, Angelo. Hiding among a tribe of the Martu in the isolation of the Australian outback near the edges of Lake Disappointment, Mouse and Angelo have seemingly evaded at least one of the predators hunting them. Carefully dropping bogus breadcrumbs across Europe, they misdirect the Novus Rishi, a ruthless cult that wants Mouse as the ultimate weapon in their battle against evil. But when unnerving dreams start to plague Angelo, and the ancient beings of the Martus Dreaming send prophetic warnings that include visions of Mouse at her fathers side, the two lovers realize its time to act. With nowhere left to run, Mouse and Angelo prepare for a last showdown with their enemies. As they chase after legendary ancient weapons ensconced in the ages old battle between good and evil, Mouse and Angelo must each decide if a final victory is worth the cost"--Book jacket.